Off with my head : the definitive basic b*tch handbook to surviving rock bottom - Schroeder, Stassi (Gallery Books, 2022)
"The New York Times bestselling author of Next Level Basic and fan-favorite alumna of Bravo's Vanderpump Rules returns from cancellation and pregnancy with the definitive Basic Bitch handbook for surviving bad days (or years)"--